Association of CASR, CALCR, and ORAI1 Genes Polymorphisms With the Calcium Urolithiasis Development in Russian Population - Litvinova, Maria M.; Khafizov, Kamil; Korchagin, Vitaly I.; Speranskaya, Anna S.; Asanov, Aliy Yu.; Matsvay, Alina D.; Kiselev, Daniil A.; Svetlichnaya, Diana V.; Nuralieva, Sevda Z.; Moskalev, Alexey A.; Filippova, Tamara V. (Frontiers in Genetics, 2021)
Kidney stone disease (KSD) is an urgent medical and social problem. Genetic factors play an important role in the disease development. This study aims to establish an association between polymorphisms in genes coding for proteins involved in calcium metabolism and the development of calcium urolithiasis in Russian population. In this case-control study, we focused on the Russian population and investigated 50 patients with calcium urolithiasis (experimental group) and 50 persons lacking signs of KSD (control group). For molecular genetic analysis we used a previously developed gene panel consisting of 33 polymorphisms in 15 genes involved in calcium metabolism: VDR, CASR, CALCR, OPN, MGP, PLAU, AQP1, DGKH, SLC34A1, CLDN14, TRPV6, KLOTHO, ORAI1, ALPL, RGS14. High-throughput target sequencing was utilized to study the loci of interest. Odds ratios and 95% confidence intervals were used to estimate the association between each SNP and KSD risk. Multifactor dimensionality reduction analysis was also carried out to analyze the gene-gene interaction. We found statistically significant (p<0.05) associations between calcium urolithiasis and the polymorphisms in the following genes: CASR rs1042636 (OR=3.18 for allele A), CALCR rs1801197 (OR=6.84 for allele A), ORAI1 rs6486795 (OR=2.25 for allele C). For the association of rs219780 polymorphism of the CLDN14 gene with the KSD development p-value was borderline (OR = 2.03 for allele C; p = 0.05). The maximum OR was shown for AA genotypes in loci rs1042636 (CASR) and rs1801197 (CALCR) (OR=4.71, OR=11.8, respectively). There was no relationship between recurrent course of the disease and family history of KSD in investigated patients. Thus we found a statistically significant association of polymorphisms rs1042636 (gene CASR), rs1801197 (gene CALCR), rs6486795 (gene ORAI1) with calcium urolithiasis in Russian Federation.